Legionella pneumophila recovery using Legiolert and a traditional culture method. Issue 3 (18th June 2021) - McCuin, Randi M.; Bartrand, Timothy A.; Clancy, Jennifer L.
Abstract: Methods for recovery and identification of Legionella spp. in water have not been improved significantly since the traditional culture method using buffered charcoal yeast extract (BCYE) agar was developed in 1979. Variations to the BCYE method include sample concentration techniques, acid and heat treatment of samples, and inclusions of antibiotics and dyes in the medium to improve Legionella recovery. A new culture method—Legiolert—was developed and is targeted specifically for recovery and enumeration of Legionella pneumophila, the pathogen responsible for >97% of Legionella pneumonia cases. This study assessed the performance of the Legiolert and BCYE methods in water samples. A total of 247 potable water samples were collected and analyzed using both methods. Mean recoveries in reagent water were similar for both methods ( 70%), while Legiolert was more likely than BCYE to detect L. pneumophila when it is present in low numbers. Article Impact Statement: The Legiolert method for enumeration of Legionella pneumophila in water is a significant improvement over the buffered charcoal yeast extract method and should be adopted.